L-shaped fiber supramolecular and its preparation method and application
The L-shaped fiber supramolecule gel addresses the limitations of existing hemostatic materials by providing rapid hemostasis and bone regeneration with enhanced stability and biocompatibility, overcoming issues of fragility and inflammatory responses.
Patent Information
- Application Number
- CN202210061127.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-19
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Existing hemostatic materials for tooth extraction sockets, such as gelatin sponge, fibrin glue, and medical collagen, suffer from slow hemostatic speed, limited functionality, and difficulty in balancing stability and efficacy, particularly in cases of massive bleeding or coagulation disorders, while self-assembling polypeptide hydrogels are fragile and easily hydrolyzed.
An L-shaped fiber supramolecule is developed, which self-assembles into nanowires under calcium ion influence, forming a gel with enhanced stability and efficacy, promoting hemostasis and bone regeneration without causing inflammatory responses.
The L-shaped fiber supramolecule gel exhibits rapid hemostasis, good biocompatibility, short degradation time, and promotes wound healing and bone regeneration, reducing local and systemic inflammation.
Smart Images

Figure CN114539361B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bioengineering, relates to a novel hemostatic functional material, and specifically relates to an L-shaped fiber supramolecule and a hemostatic functional material prepared therefrom and application thereof. Background Art
[0002] In oral clinical practice, bleeding after tooth extraction is the most common symptom during and after surgery. If not treated in time, it can lead to continuous bleeding, causing great psychological fear and serious complications to patients. The use of rapid and effective hemostatic methods after tooth extraction is crucial to the healing of extraction wounds and reducing the occurrence of complications. Packing is the most common way to treat bleeding in extraction sockets. The rational use of local hemostatic materials to fill extraction sockets is an important measure to treat and prevent bleeding after tooth extraction. At present, most tooth extraction hemostasis is achieved by compressing hemostasis by filling porous materials. Hemostatic materials can be divided into absorbable and non-absorbable types. Non-absorbable materials, such as iodoform gauze, require a second operation to remove, delaying the healing of the extraction socket, and have gradually been replaced by absorbable hemostatic materials. Commonly used hemostatic materials include gelatin sponge, fibrin glue and medical collagen.
[0003] Gelatin sponge is a non-crystalline substance extracted from connective tissues such as animal skin, bone, fascia, etc., which is processed and prepared in multiple procedures to present a porous sponge-like structure. The hemostatic principle of gelatin sponge is that the porous structure can quickly absorb a large amount of blood, promote platelet adsorption and aggregation to achieve hemostatic effect. In practical applications, gelatin sponge mainly plays a hemostatic role, and there is adhesion between the material and the tissue, which has no effect on the healing of the alveolar socket. Most materials do not have the effects of rapid hemostasis and promoting new bone formation in the alveolar socket, and it is difficult to meet the needs of accelerating the healing of the alveolar socket. In addition, some non-degradable hemostatic materials need to be removed by a second operation, which slows down the healing of the tooth extraction wound.
[0004] Fibrin glue is prepared from human or mammalian plasma, and its main components are mucin and thrombin concentrate. The hemostatic principle of fibrin glue is to simulate the body's coagulation process through high concentrations of fibrinogen and coagulation factors to form a fibrin membrane to achieve hemostasis, but its function in promoting bone regeneration is still unclear. Since the fibrin glue material itself has a coagulation effect, it can be used in patients with coagulation disorders. It should be noted that blood products have the risk of inducing immune responses.
[0005] Medical collagen is a collagen plug made of medical collagen. Its principle is that it can expand after absorbing water or blood, and can adhere to the surface of tissue to achieve a hemostatic effect. Compared with other commonly used hemostatic materials for tooth extraction sockets in clinical practice, it has a better hemostatic effect, and the collagen plug is not easy to soften in the case of heavy bleeding. Similarly, the degradation process of collagen-based tooth extraction filling materials and their role in promoting bone regeneration are unclear.
[0006] In recent years, the use of self-assembling peptide hydrogels has achieved some results in the hemostasis of large tissue and organ injuries, such as liver trauma hemostasis, because it does not require sutures and has good biocompatibility and safety, and has unique advantages as a hemostatic material. Self-assembling peptide hydrogels are driven by non-covalent weak interactions such as hydrophobic effects, electrostatic effects, and hydrogen bonding. The peptides can self-assemble and gel at the bleeding site, significantly reducing blood loss. This self-assembly driven by weak interactions into a specific network nanostructure achieves hemostasis, but the weak interactions between closed bodies make them fragile.
[0007] The existing hemostatic materials commonly used in clinical extraction sockets, such as gelatin sponges and medical collagen, mostly achieve hemostatic effects by mechanical compression, which allows the materials to swell, adhere, and coagulate blood. Although the above materials have certain hemostatic effects, some hemostatic materials are ineffective for massive bleeding or coagulation disorders, and the hemostatic materials themselves lack the mechanism to interact with the body and cannot achieve rapid hemostatic effects. As for the existing self-assembling polypeptide hydrogels, polypeptides are easily recognized and hydrolyzed by proteases due to their special molecular structure, making it difficult to balance stability and efficacy. Summary of the invention
[0008] The purpose of the present invention is to solve the problems of slow hemostatic speed, poor hemostatic effect, relatively single function, and difficulty in balancing stability and efficacy existing in existing hemostatic materials such as gelatin sponge, fibrin glue, medical collagen, and self-assembling polypeptide hydrogel.
[0009] Based on the above objectives, the present invention provides an L-shaped fiber supramolecule to solve the need in the art.
[0010] In one aspect, the present invention relates to an L-shaped fiber supramolecule, the structural formula of which is shown in formula (I):
[0011]
[0012] In another aspect, the present invention provides a method for preparing an L-shaped fiber supramolecular, comprising:
[0013] Activation of resin: soak the swollen resin in DMF for 30 minutes, filter it, and wash it with DMF and DCM alternately for 3 to 4 times;
[0014] Amino acid coupling: according to the polypeptide sequence shown in formula (I), L-amino acid is activated by HBTU / HOBT and DIEA and then added to the resin, and sequential reactions are performed to obtain a resin containing the polypeptide;
[0015] Excision and precipitation of polypeptide: the polypeptide-containing resin is placed in a cutting solution for 2 to 3 hours, precipitated with ice ether, and resuspended in 50% acetonitrile water to obtain a freeze-dried crude polypeptide; the cutting solution is calculated based on 1 mL of deionized water, and contains 1 mL of deionized water, 17.6 mL of TFA, 0.4 mL of Tips, and 0.7 g of phenol;
[0016] Isolation and purification of polypeptides: The lyophilized crude polypeptides were dissolved in 6M guanidine hydrochloride aqueous solution, separated by preparative reverse phase C18 liquid chromatography (HPLC), and the main peak products were collected.
[0017] In another aspect, the present invention relates to a gel comprising L-shaped fiber supramolecules and a calcium ion solution.
[0018] Furthermore, in a gel provided by the present invention, every 100L of 1g / L calcium ion solution is mixed with 0.5-50g of the L-type fiber supramolecule.
[0019] The present invention modifies and transforms the polypeptide to obtain an L-type fiber supramolecule, which is a calcium ion binding peptide. Under the action of calcium ions, the polypeptide sequence self-assembles into nanowires, taking into account stability and efficacy. The gel prepared by the L-type fiber supramolecule provided by the present invention has been proved by experiments to exhibit good hemostasis and biocompatibility, does not cause local and systemic inflammatory reactions when used in vivo, and has a short degradation time in the body, and has achieved the effect of promoting hemostasis, wound healing and bone regeneration. Therefore, the present invention further requests protection for the use of the gel prepared by the L-type fiber supramolecule provided by the present invention in the preparation of hemostatic materials and in the preparation of materials for promoting bone regeneration. Based on the above-mentioned applications, the present invention further requests protection for a hemostatic material, a hemostatic composition and a composition for promoting bone regeneration that can be obtained based on the present invention without inventive activities.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] The gel prepared by L-shaped fiber supramolecules provided by the present invention has been proved by experiments to exhibit good hemostasis and biocompatibility, does not cause local and systemic inflammatory response when used in vivo, has a short degradation time in the body, and has the effects of promoting hemostasis, wound healing and bone regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the result of HPLC detection of L-type fiber supramolecular.
[0023] Figure 2 This is the result of electrospray ionization mass spectrometry identification of L-type fiber supramolecular.
[0024] Figure 3 Schematic diagram of preparing gel from L-shaped fiber supramolecular; Figure 3A is the SEM characterization of L-type fiber supramolecular dissolved in CaCl2 solution with different concentrations. Figure 3 B is the result of standing for 0 to 5 days for the L-type fiber supramolecular gel.
[0025] Figure 4 This is a diagram showing the in vitro coagulation effect of the gel prepared from L-shaped fiber supramolecular; Figure 4 A is a schematic diagram of the in vitro coagulation effect. Figure 4 B is a quantitative diagram of the in vitro coagulation effect; wherein, Ctrl represents the blank control group, Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group.
[0026] Figure 5 The figure shows the results of blood routine test of rats; Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group.
[0027] Figure 6 The graph is a rat liver function test result; wherein, Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group.
[0028] Figure 7 The graph shows the renal function test results of rats one day after subcutaneous implantation of gelatin sponge or injection of L-type fiber supramolecular gel; Gelfoam represents the gelatin sponge group and L represents the L-type fiber supramolecular gel group.
[0029] Figure 8 The results of myocardial enzyme spectrum detection in rats 1 day after subcutaneous implantation of gelatin sponge or injection of L-type fiber supramolecular gel; Gelfoam represents the gelatin sponge group and L represents the L-type fiber supramolecular gel group.
[0030] Fig. 9 The figure shows the HE staining results of rat skin tissue; Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group.
[0031] Fig.10 This is the distribution diagram of bleeding time after tooth extraction in rats; Ctrl represents the blank control group, Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group.
[0032] Fig.11 This is a micro CT scan of a rat tooth extraction socket; Fig.11 A is a representative image of micro CT scan. Fig.11 B is the statistical chart of new bone percentage (BV / TV), Fig.11 C is the statistical chart of new bone thickness (TbTh), Fig.11 D is the statistical diagram of the new bone space (TbSp), Fig.11E is a statistical chart of the number of new ossicles (TbN); where Ctrl represents the blank control group, Gelfoam represents the gelatin sponge group, and L represents the L-type fiber supramolecular gel group. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is described below in conjunction with embodiments; however, the present invention is not limited to the following embodiments.
[0034] Example 1
[0035] This example provides the synthesis and preparation experiments of L-shaped fiber supramolecular.
[0036] The L-type fiber supramolecular was synthesized on a resin (Rink Amide MBHA, substitution rate 0.46mmol / g) using the HBTU / HOBt method of HBTU activation / DIEA in situ neutralization developed by FMOC-chemistry SPPS using a CS bio 336X fully automatic peptide synthesizer. The crude product was cleaved and deprotected in a reagent cocktail containing 88% TFA, 5% phenol, 5% H2O, and 2% TIPS, precipitated with cold ether (Chinese medicine), and purified to homogeneity by preparative C18 reversed-phase high-performance liquid chromatography (HPLC). The HPLC test results are as follows: Figure 1 Use a vacuum freeze dryer (cold hydrazine: -80°C, vacuum gauge: 1 Pa) to make it into freeze-dried powder and store it at -20°C for later use.
[0037] The main peak products of the liquid phase were collected for electrospray mass spectrometry identification, and 20 μL of sample was drawn into the injection bottle and inserted into the tube, wherein the liquid phase flow rate was 0.1 mL / min, the mobile phase was 50% ACN (containing one thousandth of formic acid), and the running time was 1 min; the instrument parameters were desolvation gas flow rate (L / Hr): 350, cone gas flow rate (L / hr): 30, low mass resolution LMResolution: 15, high mass resolution HM Resolution: 15, ion energy lon Energy: 0.3, capillary voltage (KV): 3.5, cone voltage Cone (V): 30, desolvation gas temperature Desolvation Temp (℃): 350; m / z range 400-1600, ionization mode ES+, and running time 1 min. Place the glass bottle containing the sample into the sample tray, name the sample in the sample list interface, set the sample volume to 5 μL and the sample location, load the method in the liquid phase method, turn on the liquid phase pump, save the file, and run the sample list. After the program is finished, click Chromatogram in the sample list to export the mass spectrometry data. The mass spectrometry data results are as follows: Figure 2By comparing the mass-to-charge ratio m / z data in the mass spectrum, we calculated whether (MW+Z) / Z was close to the corresponding mass-to-charge ratio in the spectrum, and determined that the molecular weight of the polypeptide prepared by this method was MW: 2759.04 Da, which was consistent with the compound shown in formula (I).
[0038] Example 2
[0039] This example provides a gel experiment prepared from L-shaped fiber supramolecular.
[0040] Weigh 0.5 mg and 10 mg of L-type fiber supramolecular powder, dissolve them in 100 mL of 1 mg / mL CaCl2 aqueous solution, and dissolve them by ultrasonication to prepare 0.5% and 10% (W / V) L-type fiber supramolecular gels.
[0041] 30 μL of the prepared L-type fiber supramolecular gel with a volume fraction of 0.5% and 10% was taken, diluted 100 times, and the absorbance value was detected at 280 nm. The test results are shown in Table 1. The extinction coefficients of the two polypeptides were both 1790, and there was no significant difference in their performance.
[0042] Table 1. Light absorption effect of 0.5% and 10% L-type fiber supramolecular gel
[0043] Peptides Volume fraction Absorbance at 280nm Molar concentration (mol / L) L 0.5% 1.538 8.59 L 10% 1.941 10.84
[0044] Example 3
[0045] This example provides a cross-linking degree characterization and stability verification test of L-type fiber supramolecular gel.
[0046] According to Example 2, 0.5% (W / V) and 10% (W / V) L-type fiber supramolecular gels were prepared. Ultrasonic dissolution was performed and SEM (scanning electron microscope) samples were prepared for characterization. The test results are shown in FIG. Figure 3 A. At the same time, the gel solution was left to stand for different lengths of time (0, 1, 3, and 5 days) to verify the stability of the gel. The test results are shown in Figure 3 As shown in B.
[0047] like Figure 3 As shown in the results of A, in the SEM characterization results, as Ca 2+ With the increase of concentration, the L-type fiber supramolecular fibers tend to become thicker and more densely cross-linked. Figure 3 As shown in the results of B, with the extension of time (0 to 5 days), the L-type fiber supramolecular gel solution did not change significantly, proving that the L-type fiber supramolecular gel had excellent stability.
[0048] Example 4
[0049] This example provides an in vitro coagulation effect evaluation test of L-type fiber supramolecular gel.
[0050] The experiment used 6-8 week old male rats weighing 180-220g. After the rats were anesthetized with sodium pentobarbital, blood was collected from the abdominal vein. A 3.2% sodium citrate solution was prepared and mixed at a ratio of whole blood: sodium citrate = 9:1 to prepare anticoagulated blood. The experiment was divided into a blank control group, a gelatin sponge group, and an L-type fiber supramolecular gel group. There was no significant difference in the in vitro coagulation effect of 0.5% and 10% L-type fiber supramolecular gel. In the exemplary embodiment, the volume fraction of the chiral hemostatic polypeptide gel used in the L-type fiber supramolecular gel group was 10%. After the anticoagulated blood was recalcified (anticoagulated blood: 0.2M calcium chloride = 9:1), it was slowly dripped on the surface of the hydrogel preheated at 37°C. The culture dishes containing blood samples were incubated at 37°C for 0.5min, 1.5min, 2.5min, 3.5min, 4.5min, 5min, 5.5min and 6min respectively. At the corresponding time point, 1 mL of deionized water was gently added to release free blood without disturbing the clot. The test results were as follows: Figure 4 A. The absorbance of the supernatant was measured at a wavelength of 542 nm. The results are shown in Figure 4 As shown in B.
[0051] Depend on Figure 4 It can be seen that in the in vitro coagulation experiment, compared with the natural coagulation control group and the gelatin sponge group, the results showed that the L-type fiber supramolecular gel can quickly coagulate blood within 0.5 minutes and play a hemostatic effect.
[0052] Example 5
[0053] This example provides an in vivo inflammatory response evaluation test of L-shaped fiber supramolecular gel.
[0054] The experiment used 6-8 week old male rats weighing 180-220 g. The rats were randomly divided into a gelatin sponge group and an L-type fiber supramolecular gel group, with 3 rats in each group. There was no significant difference in the in vivo inflammatory response effect of 0.5% and 10% L-type fiber supramolecular gel. In the exemplary embodiment, the volume fraction of the chiral hemostatic polypeptide gel used in the L-type fiber supramolecular gel group was 10%. After the rats were anesthetized with sodium pentobarbital, 25 mm was filled subcutaneously on the back. 3 The gelatin sponge or 50 μL L-type fiber supramolecular gel was injected. Whole blood and serum were collected 1 day later for routine blood tests and blood biochemical tests. The test results were as follows Figures 5 to 8 As shown; then skin tissues were taken for HE staining after 1 day, 3 days, and 7 days respectively. The results of HE staining test are shown as Fig. 9 shown.
[0055] One day after the rats were subcutaneously implanted with gelatin sponge or injected with L-type fiber supramolecular gel, blood was collected from each group of rats for routine blood tests. Figure 5It can be seen that by analyzing the results of blood routine tests, compared with the gelatin sponge group, the L-type fiber supramolecular gel entering the body will not cause abnormal blood cell components and will not cause inflammatory reactions. After separating the serum of rats in each group, the effects of the L-type fiber supramolecular gel on the liver function, kidney function and myocardial enzyme spectrum of rats were detected. The results showed that compared with the gelatin sponge group, the L-type fiber supramolecular gel did not cause liver (such as Figure 6 as shown), kidneys (as Figure 7 as shown) and heart (as Figure 8 damage.
[0056] After the rats were subcutaneously implanted with gelatin sponge or injected with L-type fiber supramolecular gel for 1 day, 3 days, and 7 days, the rat skin tissues were taken for HE staining. Fig. 9 It can be seen that gelatin sponge can cause inflammatory cell infiltration at the subcutaneous implantation site, and as time goes by, the local inflammatory cells increase. Fig. 9 It can be found that the degradation of gelatin sponge is limited within 7 days. Fig. 9 The results showed that the inflammatory cell infiltration of the L-type fiber supramolecular gel increased in the first three days, and decreased significantly after 3 days. The volume of the L-type fiber supramolecular gel decreased. By comparing with the gelatin sponge group, it was found that the local inflammatory cells in the L-type fiber supramolecular gel group were significantly reduced.
[0057] Example 6
[0058] This example provides an evaluation test of L-shaped fiber supramolecular gel in vivo hemostasis and bone healing and regeneration promotion.
[0059] The experiment used 6-8 week old male rats weighing 180-220 g. The rats were randomly divided into a blank control group, a gelatin sponge group, and an L-type fiber supramolecular gel group. After sodium pentobarbital anesthesia, the maxillary right incisor was extracted. The gelatin sponge group filled the extraction socket with 10 mm 3 The L-type fiber supramolecular gel group was quickly injected with 50 μL of L-type hemostatic gel, and the blank control group was not treated. There was no significant difference in the in vivo hemostasis and bone healing regeneration effects of 0.5% and 10% L-type fiber supramolecular gel. In this exemplary embodiment, the volume fraction of the chiral hemostatic polypeptide gel used in the L-type fiber supramolecular gel group was 10%. After complete hemostasis, the bleeding time was recorded, and the results were recorded as follows: Fig.10 One month later, the maxillary tissue of the rats was taken and fixed, and then micro CT scan was performed to observe the healing of the extraction socket. The results are shown in Fig.11 shown.
[0060] Depend on Fig.10It can be seen that compared with the control group, the L-type fiber supramolecular gel can significantly reduce the bleeding time after tooth extraction. One month after the rats were extracted, the maxillary extraction socket tissue of the rats was taken for micro CT scanning. The scanning results are shown in Fig.11 A. By Fig.11 B~ Fig.11 E It can be seen that compared with the gelatin sponge group, the L-type fiber supramolecular gel can promote the regeneration of new bone in the alveolar socket, increase the thickness and number of new ossicles, and reduce the gap between new ossicles.
[0061] As described above, the present invention can be well implemented. The above embodiments are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention. Sequence Listing <110> Shaanxi Future Peptide Biotechnology Co., Ltd. <120> L-shaped fiber supramolecular and its preparation method and application <140> 2022100611279 <141> 2022-01-19 <160> 1 <170> SIPOSequenceListing 1.0 <210> 1 <211> 26 <212> PRT <213> Artificial Sequence <400> 1 Arg Ala Asp Ala Arg Ala Asp Ala Arg Ala Asp Ala Arg Ala Asp Ala 1 5 10 15 Gly Ser Val Leu Gly Tyr Ile Gln Ile Arg 20 25
Claims
1. A gel for use in preparing materials for hemostasis of tooth extraction sockets and promoting new bone regeneration in alveolar sockets, characterized in that: The gel is composed of L-type fiber supramolecules and calcium ion solution, the amino acid sequence of the L-type fiber supramolecule is shown in SEQ ID NO: 1, and the L-type fiber supramolecule is composed of L-type amino acids; The gel is prepared by mixing 1 g / L of the calcium ion solution with 0.5-10 g of the L-type fiber supramolecule per 100 L.
Citation Information
Patent Citations
Polypeptide, and synthesis method and application thereof
CN111574591A
Functional self-assembled nano-polypeptide hydrogel, preparation method, application and preparation
CN113633823A
Cited By
Intelligent feedback drug delivery system for oral environment and preparation method thereof
CN121714528A
